Penerapan Model Problem Based Learning Untuk Meningkatkan Minat Belajar Pada Materi Menulis Teks Laporan Hasil Observasi Siswa SMP - Rizqy Dwi Ariyanti (Piwulang Jurnal Pendidikan Bahasa Jawa, 2025)
This study aims to examine the implementation process of the problem-based learning model in teaching how to write observation report texts in class, as well as to identify whether the application of the problem-based learning model can enhance students' interest in learning this material. This research uses a qualitative approach with a descriptive method, involving observation, interviews, and documentation as data collection techniques. The data sources for this study are 28 students from class VIII Sains 3 at MTs Negeri Surakarta 1. The data collected were then analyzed using qualitative descriptive analysis to describe the situation and learning process. The results of the study show that the application of the problem-based learning model in teaching observation report texts has a significant positive impact on students' learning interest. This model was proven effective in addressing the problems faced by students, such as boredom in learning and difficulty in composing systematic and clear texts. The level of student engagement during the learning process was very high, as reflected in the enthusiasm of students to ask questions and actively participate in each stage of the learning process. The implications of this study also provide insights for educators and policymakers in designing more innovative and student-centered teaching methods to improve the quality of education in schools.